KERALA ECOTOURISM: A PROMISING SUSTAINABLE LIVELIHOOD OPTION IN RURAL LABOUR MARKET - Dr. Jenni K. Alex (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Ecotourism is an efficient mechanism for sustainable development and this is the key reason why developing countries are espousing and including it in their myriad of economic development and conservation strategies. Ecotourism has been promoted as a socially compatible tourism strategy for sustainable development and besides it has emerged as a source of livelihood for the informal workers. The present study analyses how ecotourism intervenes and brings about localized structural changes in Kerala's rural labour market. The findings of the study are aggregation of primary data collected from 872 casually employed workers from 29 ecotourism destinations of Kerala. The zone-wise (North, Central and South) analysis reveals that ecotourism has ensued localized changes in the rural informal labour market of Kerala. Moreover, the involvement of local community in ecotourism helps in the conservation of the ecology and biodiversity of the area which in return provides economic incentives to the local community. To sum up, ecotourism initiatives across Kerala have brought structural changes in the rural informal labour market by generating reasonable employment opportunities associated with them.